2012
DOI: 10.1007/s11340-012-9617-1
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Digital Image Correlation for High-Resolution Strain Mapping of Ceramic Composites

Abstract: Digital image correlation (DIC) is assessed as a tool for measuring strains with high spatial resolution in woven-fiber ceramic matrix composites. Using results of mechanical tests on aluminum alloy specimens in various geometric configurations, guidelines are provided for selecting DIC test parameters to maximize the extent of correlation and to minimize errors in displacements and strains. The latter error is shown to be exacerbated by the presence of strain gradients. In a case study, the resulting guidelin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(52 citation statements)
references
References 28 publications
2
48
0
2
Order By: Relevance
“…Baseline tensile properties were also measured at ambient temperature with periodic unloading‐reloading excursions to measure hysteresis. Displacement and strain fields were measured by digital image correlation following procedures described in detail elsewhere . These tests were used to ascertain stresses associated with cracking of the outer SiC overcoat.…”
Section: Materials Test Procedures and Analysesmentioning
confidence: 99%
“…Baseline tensile properties were also measured at ambient temperature with periodic unloading‐reloading excursions to measure hysteresis. Displacement and strain fields were measured by digital image correlation following procedures described in detail elsewhere . These tests were used to ascertain stresses associated with cracking of the outer SiC overcoat.…”
Section: Materials Test Procedures and Analysesmentioning
confidence: 99%
“…After drying, black paint was sprayed quickly past the surface in a sweeping motion using an air brush, creating a high-contrast speckled pattern. Full image correlation requires that the speckle size be small enough in the deformed image such that, each subset contains sufficient unique information [22]. Speckle size was controlled by modifying the nozzle, air pressure, and throttling the spray.…”
Section: Study Of Strain Gradients In a Bonded Joint Using Digital Immentioning
confidence: 99%
“…First, there is measurement error associated with digital image correlation. For typical values of displacement noise and the filter length employed in the strain calculation (h f ¼ 1 mm), the strain error in regions of relatively uniform strain should be on the order of a few hundred microstrain [37]. This value is evidently insufficient to explain all of the strain inhomogeneity.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, there are also non-stochastic effects associated with the woven fiber architecture. [37] observed that, in 2-D woven composites, local strain enhancement occurs at tow 'crossovers': locations where undulating warp tows dive beneath flat weft tows. Similar effects may be responsible for the strain 'hotspots' observed in Fig.…”
Section: Resultsmentioning
confidence: 99%